Geographic Information System of UMKM Location Mapping in Sidoarjo Regency - Moch Eko Budi Setiawan; Ika Ratna Indra Astutik (Procedia of Engineering and Life Science, 2022)
Sidoarjo Regency is an area that has a large number of MSMEs. Culinary and handicraft SMEs are widespread in 18 sub-districts in Sidoarjo Regency, numbering in the thousands. There are still a few MSMEs who understand how to promote online, and some MSMEs have gone out of business due to a lack of consumers. Many of the people of Sidoarjo still don't know the location of MSMEs because the location of MSMEs in villages and far from urban areas makes MSMEs unable to develop due to lack of customers. From that problem, the author's goal is to create a geographic information system for MSMEs in Sidoarjo to promote their products to the wider community in Disidoarjo and at the same time provide information on the location of MSMEs. In making this system, it was created using the CodeIgniter framework and MySQL as the database to store MSME data. The results of this study are that it is easier for people to find information on MSMEs in Sidoarjo Regency and with an interesting and interactive information system that can be accessed in various places, whenever and wherever so that they can help MSMEs for their products to be known more broadly, specifically for the Sidoarjo Regency and can also increase sales of MSME products.